FAIRY TALE AS A SOURCE OF FORMATION OF MAN’S SPIRITUAL CULTURE - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article deals with the aesthetic nature of a fairy tale as a source of formation of spiritual culture of man.